Tuberculous meningitis in an immunocompetent male complicated by hydrocephalus. (7th October 2016) - Dunphy, Louise; Shetty, Prashanth; Randhawa, Rabinder; Rani, Kharil Amir; Duodu, Yaw
Abstract : A 39-year-old man, born in India but resident in the UK for 10 years, was travelling in America when he became feverish with an altered mentation. He reported a 10-day history of fever, photophobia, headache and fatigue. His medical history included hypothyroidism and migraine. He was a non-smoker, did not consume alcohol and denied a history of drug use. He was transferred to the emergency department. Laboratory investigations confirmed hyponatraemia (sodium 128 mmol/L). A chest radiograph confirmed no focal consolidation. Further investigation with a CT brain was unremarkable. A lumbar puncture was suggestive of viral meningitis, with a raised white cell count, lymphocytosis, high protein and low glucose. His PCR was negative for enterovirus and herpes simplex virus. Further investigation with a CT thorax, abdomen and pelvis demonstrated bilateral upper-lobe infiltrations. A bronchoalveolar lavage was negative for acid alcohol fast bacilli (AAFB). A diagnosis of tuberculous meningitis was rendered following a repeat lumbar puncture. Gram stain revealed AAFB and PCR was also positive. He started antitubercular treatment and corticosteroids. A repeat CT brain demonstrated ventriculomegaly, suggestive of hydrocephalus and an MRI head revealed likely communicating hydrocephalus with basilar enhancement. He was repatriated to the UK. Eleven days post transfer, he became acutely confused and required external ventricular drain insertion. After surgical management of his hydrocephalus, there was no further neurological deterioration. He remains committed to his neurorehabilitation.